SALTMOD Model Validation and Application in Segwa Minor Canal Command Area - Shrivastava, P K; Patel, A M; Oosterbaan, R J (Journal of Agricultural Engineering, 2002)
Model SALTMOD was validated by comparing model predictions with the field observations on soil salinity and drain discharges and depth of water table collected during 2000 - 01, for the Segwa minor canal command. After installation of drainage system, soil salinity of root zone was found to reduce from 12 dS/m to around 7 dS/m in the first year, which was also predicted by the model, similarly the model predicted steady increase on salinity levels each year which was confirmed from field tests. The model forecasts salinity levels of 8 dS/m by 2010 thus making the land uncultivable, if precautionary measures are not taken in the canal command area. Investigations were made to study the impact of drain spacing in the form of Q/H relations, drain depth, depth of irrigation water application on soil salinity. It predicts that at 45 m drain spacing the depth of drains should be at least 1.2 m below ground level, for irrigation water quality of 0.9 dS/m, for maintaining the salinity levels at around 2.5 dS/m. The model also shows that salinity levels of 2.5 dS/m could be maintained if irrigation water supplies (IWS) remain at least 20 % lower. Therefore, SALTMOD could work as an effective tool to forecast various situations once the model is calibrated and validated for the region and could help during design of drainage system.